Students' Perceptions towards National Examination: A Washback Study - Friska, Yuliana; Setiawan, Iwan (Universitas Swadaya Gunung Jati, 2018)
This study aimed to investigate students’ perception towards the National Examination (Ujian Nasional/UN) and its positive and negative effects (washback). The study was a qualitative research using a survey method. It involved XII-grade students who had taken the examination from some vocational senior high schools in East Ciputat, South Tangerang, Banten, i.e. SMK Triguna Utama, SMK YMJ and SMK Moh. Husni Thamrin. A questionnaire was therefore constructed to elicit their beliefs, attitudes, behaviors and/or opinions regarding the UN. The findings showed almost all of the students believed that National Examination could increase their learning intensity, or, in other words, UN could motivate them to study harder. However, there was also revealed that the students doubted and questioned the effectiveness and importance of UN in creating better teaching learning process. These thus indicated that National Examination had positive as well as negative washback on teaching learning activities of XII-grade students of some vocational senior high schools in South Tangerang.